STUDY OF TOXICOLOGY OF THE ANTITUMOR DRUG COLCHIPRIT-NEO (K-20) - Leonidovna, Vypova Natalia; Nishanov Danier Anarbaevich; Madaliev Akhror Alievich; Ibragimov Shavkat Narzikulovich; Enikeeva Zulfiya Makhmudovna; Urozov Nuriddin Elmuratovich (PT. Antis International Publisher, 2024)
Objective: Colchiprit-neo was administered orally to rats at dosages of 30.0, 61.0, and 120 mg/kg for 30 days in order to assess its chronic toxicity. Methods: The effects on behavior, body weight, peripheral blood composition, kidney function, liver enzyme levels, and internal organ pathology were evaluated after rats were given Colchiprit-neo at the recommended dosages. To assess the reversibility of any possible harmful effects, a one-month recovery time was incorporated. Results: According to the study, rats' behavior, body weight, and blood composition were unaffected by repeated oral treatment of Colchiprit-neo. During therapy, the liver's alanine aminotransferase (ALT) level rose, but during the recovery phase, all tested values went back to normal. The 30 mg/kg dose did not cause any toxicity in the parenchymal organs, according to pathomorphological analysis. Novelty: The findings indicate that Colchiprit-neo is safe for long-term usage because it does not show substantial chronic toxicity at therapeutic levels. This work offers significant preclinical evidence in favor of its possible therapeutic use without endangering the major organ systems.